Voices of Resistance : Testimonies of Cuban and Chilean Women - Maloof, Judy, 1957- (Book collections on Project MUSE., 1999)
Latin American women were among those who led the suffrage movements of the nineteenth and early twentieth centuries, and their opposition to military dictatorships has galvanized more recent political movements throughout the region. But because of the continuous attempts to silence them, activists have struggled to make their voices heard. At the heart of Voices of Resistance are the testimonies of thirteen women who fought for human rights and social justice in their communities. Some played significant roles in the Cuban Revolution of 1959, while others organized grassroots resistance to.